THE LOCAL OPTIMIZATION OPERATION ON PARTS OF THE RAILWAY - Lashkov, O. V.; Kotsar, O. A. (Science and Transport Progress, 2006)
An issue of optimization of local work as the main part of transportation process has been considered. A complex of actions aimed at improving its indices has been offered. The key attention has been paid to a question of advisability of assigning the unplanned dispatch trains.